ESP curriculum in Accounting Study: Exploring Alumni's Needs of Learning - Erna Nawir; Wenny Elsara; Dessy Dwisusila (Journal of English Language and Education, 2023)
The absence of clear curriculum guidelines for ESP education in Indonesia, particularly at the university level, has prompted the need for a needs analysis from alumni, particularly in the field of accounting, as one of the important stakeholders in ESP curriculum design. Through a mixed approach with convergent design, data obtained from questionnaires and interviews involving 14 alumni, 5 instructors, and a head of the accounting department revealed that the alumni strongly require language proficiency and good language skills, with an equal percentage of 84.28%. This was followed by the desire for relevant vocabulary and suitable learning themes that align with their professional environments, with percentages of 78.57% and 77.16% respectively. In a nutshell, the alumni require specific language proficiency and skills in their respective fields, supported by adequate vocabulary and relevant learning themes as input in designing an ESP curriculum, especially in the field of accounting.